Magyarország kommunikációs tengelyeinek alakulása - Erdősi, Ferenc (Tér és Társadalom, 1996)
The analysis of the more than thousand-year-long history of traffic in the Carpathian basin (the historical Hungary) has proved that in spite of the significant changes that have taken place in our relative economic geographical situation within the continent, in the development of the main axes of transportation both the signs of continuity and discontinuity, working against one another, can be shown. This means that there was – regardless of the ages – a certain visible continuity, stableness, in fact, the "conservative" elements of the network are still present and functioning, but following the change of orientation in foreign policy and foreign economy (and only to small extent due to the rearrangement of the regional division of labour within the "inner economy") many an axis of communication changed considerably in importance, in which process the development of transportation technology and the appearance of new means of transportation only played a subordinate role. The basic direction of the main axes and channels of transportation was injluenced by the transcontinental transit traffic and the already long existing mono-central structure of Hungary, while natural endowments (relief, river system) only played a secondary role, diverting and modifying the basic direction in some places. The axes and channels are "tied up" complexes of the tracks and cables of more and more subsectors and means of communications (rail, road, in some places inland navigation, pipelines, transmission lines, telecommunication lines). The dominant elements of there "bunches" are usually the main rail lines that were the first to be built and later attracted the other means of communication to themselves. This attraction, however, is declining in significance, thus the latest means of communication (pipelines, transmission lines, telecommunication lines) do not "cling" to them closely and parallel but only follow their rough direction, mainly it is only vectoral similarity that can be seen. In the formation of the dominant track complexes of our communication macro-structure, in the beginning spontaneity played some role in the creation of natural roads, paths, as did later intuition based exclusively on experiences. From the "artificial" track constructions starting with the Enlightenment (in the era – made up by several periods – of the capital intensive transportational infrastructural investments) approaching the present days, the high level of consciousness appearíng in stricter and stricter planning is typical. of course it was always ex post practice, the experiences of the application that decided whether the direction of the created main axes were actually suitable for the vectors of the actual flows of material, persons and information and for their generating lines, and if so, how long?